Primary school students' attitudes towards peers displaying hyperactivity: Examining impacts of homophily and inter‐group contact on students' social inclusion. Issue 3 (2nd February 2022) - Hassani, Sepideh; Schwab, Susanne; Boda, Zsofia
Abstract: Earlier research has indicated that students displaying hyperactivity struggle with their social inclusion. To foster social inclusion, students' attitudes as well as inter‐group contact have been identified as possible key factors. In this study, the social inclusion of students who display hyperactivity in general and classmates' attitudes towards such peers have been investigated. Data of 314 students (aged 9–11) and estimated dynamic social network models for the co‐evolution of friendships and attitudes are relied on. Results reveal that students displaying hyperactivity are at risk of lower social inclusion. Results do not indicate that having friends or classmates who display hyperactivity is significantly associated with one's attitudes towards such peers in either causal direction.